The Galactic Disk North–South Asymmetry in Metallicity May Be a New Tracer for the Disk Warp - Sun, Weixiang; Shen, Han; Jiang, Biwei; Liu, Xiaowei (Astrophysical journal. Letters, 2025)
Galactic disk warp has been widely characterized by stellar distributions and stellar kinematics but has not been traced by stellar chemistry. Here, we use a sample with over 170,000 red clump (RC) stars selected from LAMOST and APOGEE first to establish a correlation between the north–south asymmetry in metallicity ([Fe/H]) and the disk warp. Our results indicate that the height of the [Fe/H] midplane for the whole RC sample stars is accurately described as Z w = 0.017 ( R  − 7.112) 2 sin( ϕ  − 9.218). This morphology aligns closely with the warp traced by Cepheids, suggesting that the disk north–south asymmetry in [Fe/H] may serve as a new tracer for the Galactic warp. Our detailed analysis of the young/thin disk stars of this RC sample suggests that its warp is well modeled as Z w = 0.016 ( R  − 6.507) 2 sin( ϕ  − 4.240), indicating that the line of node of the Galactic warp is oriented at 4.240 − 1.747 + 1.641 degrees.